PENGARUH MATA PELAJARAN AQIDAH AKHLAK TERHADAP HASIL BELAJAR DAN KECERDASAN EMOSIONAL SISWA MI MWB MRONJO SELOPURO BLITAR TAHUN AJARAN 2022/2023 - Imam Taufiq; Sholichin; Rizka Khuswanal Mala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Aqidah Akhlak subject on learning outcomes and emotional intelligence of students at MI MWB Mronjo Selopuro Blitar. The study uses a quantitative approach with data collection techniques through questionnaires, interviews, and documentation. The Aqidah Akhlak learning process does not only focus on cognitive aspects, but also on the formation of attitudes and emotional intelligence of students which are influenced by the role of teachers, students, the madrasah environment, and learning strategies. The results of the study indicate that Aqidah Akhlak learning has a fairly good influence on learning outcomes with an average value of 46 and emotional intelligence with an average value of 47. The religious madrasah environment is the main supporting factor, while the low awareness of learning and polite attitudes of some students are inhibiting factors. Hypothesis testing shows a significant influence of Aqidah Akhlak learning on learning outcomes and emotional intelligence of students at MI MWB Mronjo Selopuro Blitar.